Managing chronic pain in an age of addiction - Purvez, Akhtar (Rowman & Littlefield, 2018)
As a nation, we are facing an unprecedented opioid crisis that is killing more than 65,000 people a year. It is destroying our families and decimating our neighborhoods. And it is costing us billions. As more and more people are dealing with chronic pain, and as the opioid crisis reaches epic proportions, alternative approaches to understanding pain and its management are necessary. Here, Dr. Akhtar Purvez, a seasoned researcher, pain specialist, and pain advocate, offers basic information about pain and pain conditions and considers how we approach pain from cultural, biological, and medical perspectives. He discusses the latest minimally invasive, interventional approaches like nerve blocks and ablation procedures, and neuromodulation techniques like peripheral nerve, spinal cord, and brain stimulation. The uses of marijuana and associated interventions is reviewed, and Purvez walks readers through the process of assessing pain, finding a doctor who can treat it, and methods for coping with pain through non-medical approaches like meditation. Anyone coping with pain or helping someone who is will find here a ready resource that offers hope and understanding.